EP.FRI.821 Operative Treatment of Abscesses – Optimising A Timely Route to Theatre. (28th October 2021) - Ikram, Hamza; Taylor, Roland; Dosis, Alexios; Robinson, Jonathan
Abstract: Aim: 1st audit cycle to assess whether patients presenting to the acute surgical service had their abscesses incised and drained in a prompt and timely manner. To develop a pathway for improving efficiency Methods: All general surgical patients admitted to the surgical admissions unit between 1st September and 31st October 2020 by reviewing clinical and operative notes. Only those patients that had abscesses drained under general anaesthesia. Other specialties abscesses were excluded. Guidelines from the American Society of Colon and Rectal surgeons for draining abscesses acutely were used. Data was collected on various parameters.  Results: A total of 62 patients had abscesses drained. The mean age of patients was 32 years. The average waiting time between decision to operate and surgery was 14 hours and 54 minutes. 19% of the patients were sent home after decision was made to operate and brought back in the morning. Conclusion: This 1st audit cycle concludes long waiting times and unnecessary overnight stay. A re-audit will be carried out using the same parameters in March 2021. Implementing a dedicated general surgical abscess pathway for patients without significant co-morbidities will improve efficiency and patient satisfaction. References   1. Kumar C, Page R, Smith I, Stocker M, Tickner C, Williams S, et al. Day case and short stay surgery: 2. Anaesthesia. 2011;66(5):417–34.  2. Balakumar R, Samuel N, Jackson A, Butterworth J, Shiwani MH. Day-surgery approach for incision and drainage of an abscess. Surg Pract. 2016;20(4):157–60.